Evaluation of Soybean Mutant Lines for Resistance to Stink Bugs (Hemiptera: Pentatomidae) - Vicentin, Ignacio Gabriel; Cuatrin, Alejandra; Ghione, Celina Elena; Lombardo, Lucio; Saluso, Adriana (Ediciones INTA, 2025)
Soybean is one of the main oilseed crops in the world, and stink bugs complex can cause an important reduction in seed yield and quality. The primary control strategy against this pest consists in the use of insecticides according to the economic damage thresholds established for each species. Additionally, genetic resistance allows a more friendly agriculture, reducing the applications of insecticides, contamination, and production costs. To date, only a few genotypes with polygenic resistance are known, and they were introduced in soybean breeding programs. However, there are no records of the use of induced mutation techniques to obtain a new variability for resistance to stink bugs. The aim of this study was to evaluate mutant soybean lines for resistance to stink bug complex, generated by chemical mutation with ethyl methane sulfonate (EMS). The field experiments with six replications were conducted in 2020/21 and 2021/22 in Oro Verde, Argentina. Forty-one genotypes, including mutant lines, experimental lines and resistant and susceptible cultivars were evaluated. Variations among years, genotypes and their interaction were observed for the duration of the phenological cycle, height, lodging, 100 seed weight (100-wt), yield and percentage of damaged seeds. The mutant lines showed variability in the percentage of damaged seeds between 36.8–57.8%. The mutant line Mut12 showed the best performance with an average of 38.8% of seed damage, and was located among the six genotypes with less seed damage, including the wild-type line LAE9758803-B. We confirm that induced mutant lines could present variability for resistance to stink bugs that may complement the study and development of new sources of resistance. The mutant line Mut12 could be used as breeding material in different breeding programs, and future studies should be done to understand the type of resistance that it has.